The impact of Prader–Willi syndrome on the family's quality of life and caregiving, and the unaffected siblings' psychosocial adjustment. (12th October 2012) - Mazaheri, M. M.; Rae‐Seebach, R. D.; Preston, H. E.; Schmidt, M.; Kountz‐Edwards, S.; Field, N.; Cassidy, S.; Packman, W.
Abstract Background Prader–Willi syndrome (PWS), a complex multisystem genetic disorder, is characterised by developmental abnormalities leading to somatic and psychological symptoms. Symptoms of PWS include infantile hypotonia and failure‐to‐thrive, followed by life‐long hyperphagia, developmental delays and moderate‐to‐severe behavioural problems and several physical problems that impact health. This study examined the effects of caring for a child diagnosed with PWS on the mothers and unaffected siblings. We assessed overall family functioning, the mothers' psychological health, the psychosocial and behavioural functioning of siblings, and the quality of life of siblings. Methods Participants included 12 mothers and 13 siblings of a child with genetically confirmed PWS. Self‐report measures administered to the mothers evaluated overall family functioning (PedsQL – Family Impact Module), the mothers' psychological health (Brief Symptom Inventory), and the mothers' perception of the sibling's quality of life (PedsQL – Parent Proxy). Self‐report measures administered to the siblings evaluated their perceived quality of life (PedsQL) and symptoms of post‐traumatic stress disorder (PTSD) (UCLA PTSD Index). Results Families/mothers/siblings with children with PWS showed poorer perceived quality of life compared with general inpatient and outpatient samples of children with complex health conditions. Families/mothers/siblings with children with PWS reported difficulties in family functioning, communication problems, and an increased number of conflicts. They appeared to be experiencing significant behavioural distress symptoms, with higher than average levels of depression and feelings of isolation, anger and worry. Ninety‐two per cent of the siblings indicated moderate‐to‐severe symptoms of PTSD. Compared with normative populations, siblings demonstrated poorer quality of life, with mothers perceiving more significant deficits in the sibling. Conclusion This study reaffirms that PWS affects the entire family system. Mothers and siblings would benefit from psychosocial support due to the multiple challenges of living with and caring for a child/young adult with PWS.